2016
DOI: 10.1111/jace.14370
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Vitruvius: New Insight in the Technology of Egyptian Blue and Green Frits

Abstract: Archeological campaigns along the track of the Domitian road in Cuma resulted in the recovery of a large amount of potshards and crucible fragments (both open and closed forms), covered with residues of blue and green frits, respectively. Typological analysis of the crucibles combined with mineralogical and petrological analyses on the ceramic body and frit residues revealed that the forms are intimately related to the technological data. Newly formed calcium silicates indicate high firing treatments of crucib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 24 publications
4
34
0
2
Order By: Relevance
“…Taking into consideration the textural features (sorting and circularity) and the mineralogical assemblage, such a mixed‐source temper resembled the shoreline deposits from Mondragone to north of Cuma, where beach sands are affected by the flux of siliciclastic and carbonate sediments of the Volturno River with a volcanic component derived from Campanian volcanoes (Balassone et al, ; Morra et al, ). It is worth highlighting that such sand was a valuable geomaterial, largely used in antiquity by Phlegraean artisans (including Cuma) as starting materials for glass and green/blue pigments, as also claimed by Vitruvius (Grifa et al, ). Hence, the cooking pots of presumed Aegean‐like tradition can be considered as imitations since the artifacts from the Eastern Mediterranean pottery tradition are sensibly different as characterized by the occurrence of metamorphic or acidic volcanic‐tempered pastes (Istenič & Schneider, ); moreover, they also differ from other Italian imitations, in which a calcareous paste plus volcanic temper was recognized (Gliozzo et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Taking into consideration the textural features (sorting and circularity) and the mineralogical assemblage, such a mixed‐source temper resembled the shoreline deposits from Mondragone to north of Cuma, where beach sands are affected by the flux of siliciclastic and carbonate sediments of the Volturno River with a volcanic component derived from Campanian volcanoes (Balassone et al, ; Morra et al, ). It is worth highlighting that such sand was a valuable geomaterial, largely used in antiquity by Phlegraean artisans (including Cuma) as starting materials for glass and green/blue pigments, as also claimed by Vitruvius (Grifa et al, ). Hence, the cooking pots of presumed Aegean‐like tradition can be considered as imitations since the artifacts from the Eastern Mediterranean pottery tradition are sensibly different as characterized by the occurrence of metamorphic or acidic volcanic‐tempered pastes (Istenič & Schneider, ); moreover, they also differ from other Italian imitations, in which a calcareous paste plus volcanic temper was recognized (Gliozzo et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…The ancient production of Egyptian blue must have been in the hands of very competent specialists and large workshops for its production has been identified in Amarna and elsewhere . Egyptian blue synthesis requires the firing of a mixture of a copper salt, calcium carbonate, and quartz usually with a small amount of a sodium flux to temperatures between 850 and 1,050 . Frit cakes of the pigment from the 2nd Millenea BCE from Egypt have been studied by Hatton et al, and these cakes would be ground to produce the pigment with large particle sizes reported to be as large as 150 μm.…”
Section: Notes On the Production Of Egyptian Blue And The Particle Sizementioning
confidence: 99%
“…Two experimental methods have recently been reported for the production of the pigment described by Johnson‐McDaniel et al: The melt‐flux method requires lower temperature (875 °C) and produced smaller sized particles in the laboratory (5–15 μm crystallites by SEM), whereas solid state synthesis yielded larger particle sizes (15–50 μm) but requires higher synthesis temperatures (1020 °C), thus above the melting point of bronze. In archaeological studies, Grifa et al demonstrated that high temperatures were achieved in synthesis using crucibles from Cuma, thus exceeding the thermal stability of cuprorivaite crystals (950–1050 °C), thus within the range for both synthesis routes.…”
Section: Notes On the Production Of Egyptian Blue And The Particle Sizementioning
confidence: 99%
“…Außergewöhnliche chemische Kreativität wurde aufgewendet, um Pigmente und Farbstoffe für Farben zu produzieren, die nur selten als stabile Verbindungen in der Natur auftreten. Die Suche nach Alternativen für die teuren blauen Pigmente Lapislazuli, Indigo und Azurit ist besonders anschaulich und führte zu der sehr frühen und innovativen Entwicklung von chemischen Synthesen: Ägyptisch Blau, Han‐Blau, und Maya‐Blau, Cobaltmineralien und –gläser (Cobalt und Coelinblau, Cobaltglas), türkisfarbenes Elfenbein und, in jüngerer Zeit, das Eisencyanid Preußischblau, Phtalocyanine bis hin zum zeitgenössischen International Klein Blue. Ein besonderer Grad an “Perfektion” hinsichtlich der optischen Eigenschaften wurde durch die inspirierenden frühen chemischen Synthesen erreicht, die für die gegenwärtige Materialchemie von besonderem Interesse sind .…”
Section: Künstliche Materialien Mit Bemerkenswerten Eigenschaftenunclassified
“…Die Suche nach Alternativen für die teuren blauen Pigmente Lapislazuli, Indigo und Azurit ist besonders anschaulich und führte zu der sehr frühen und innovativen Entwicklung von chemischen Synthesen: Ägyptisch Blau, Han‐Blau, und Maya‐Blau, Cobaltmineralien und –gläser (Cobalt und Coelinblau, Cobaltglas), türkisfarbenes Elfenbein und, in jüngerer Zeit, das Eisencyanid Preußischblau, Phtalocyanine bis hin zum zeitgenössischen International Klein Blue. Ein besonderer Grad an “Perfektion” hinsichtlich der optischen Eigenschaften wurde durch die inspirierenden frühen chemischen Synthesen erreicht, die für die gegenwärtige Materialchemie von besonderem Interesse sind . Ein ähnlich interessantes Beispiel sind frühe islamische Glasuren, die überall für ihren goldenen Schimmer bekannt sind, der durch eine Optimierung der Oberflächenplasmonenresonanzeffekte von Kupfer‐ und Silbernanopartikeln erhalten wird, die an der Glasuroberfläche gebildet werden .…”
Section: Künstliche Materialien Mit Bemerkenswerten Eigenschaftenunclassified